Living through crises due to successive commodity booms and busts: Investigating the changing peasants' farming style in rural Indonesia - Tualle, Muchlas Dharmawan; Mujetahid, A.; Dassir, Muhammad; Sirimorok, Nurhady; Muhammad, A. Khalid; Muin, Andi Vika Faradiba; Prasetyo, Aryo Dwi (Forestry Faculty, Universitas Hasanuddin, 2023)
This study aims to explain how a peasant community makes decisions in response to recurring crises in order to maintain their farms, and the extent to which vulnerability contexts and (external) institutions influence peasants’ decision-making regarding their livelihoods. In doing so, we present a case study of the Village of Ranga, in the South Sulawesi Province, Indonesia, where data collected through semi-structured interviews, observation, and Focus Group Discussion (FGD). Data regarding farmers' livelihood strategies in responding to the crises, in the form of commodity booms and busts, is analyzed by employing a sustainable rural livelihoods framework, while a Chayanovian “balance” approach is used to understand peasants’ decision making and the extent to which they retain operations as ‘peasant farms’. We found that the most critical vulnerability that directly contributes to changes in the peasants' livelihood trajectories is successive shocks in the form of physical disturbances to plants and land. In making decisions regarding changes in livelihood strategies when facing crises, farmers seem to be pushed to abandon various balances they previously upheld, except to some extent the labor-consumption balance. This change potentially deepens the vulnerability of the Ranga Village peasants by adding more exposure to volatile markets and environmental pressure (such climate-induced hazards, pests, disease, and water crisis). This research can help us to understand the nature of the peasant responses in times of crises, and therefore help to inform the scanning of potential strategic measures for rural agricultural development in order to increase agricultural resilience.